Regional Original Income and Special Allocation Funds on Economic Development - Zainuddin Rahman (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to determine whether there is a natural and significant effect of Regional Original Income (PAD) and Special Allocation Funds (DAK) on Economic Development in Pinrang Regency and find the most dominant variables affecting economic development in Pinrang Regency. This research was conducted at the Regional Personnel Agency of Pinrang Regency. The type of data used in this study is secondary data, namely data sourced from documents, publications, or unique publications from related agencies, especially in Pinrang Regency. Data collection techniques in this study use the method of documentation. The data that has been collected will be tested by several stages of testing, namely descriptive statistical tests, classical assumption tests consisting of (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), and testing all hypotheses through the coefficient of determination test, partial test (t-test ) and simultaneous test (f test). The results showed that the Regional Original Income (PAD) variable significantly affected economic development in Pinrang Regency. Meanwhile, the Special Allocation Fund hurts economic growth in the Pinrang district.